Nanoparticle-conjugated aptamer targeting hnRNP A2/B1 can recognize multiple tumor cells and inhibit their proliferation. (September 2015) - Li, Hui; Guo, Lei; Huang, Aixue; Xu, Hua; Liu, Xuemei; Ding, Hongmei; Dong, Jie; Li, Jie; Wang, Chaonan; Su, Xueting; Ge, Xingfeng; Sun, Leqiao; et al.
Abstract: In this study, we further investigated a previously developed aptamer targeting ROS 17/2.8 (rat osteosarcoma) cells. We found that this C6-8 aptamer specifically binds to heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1 and that it specifically labeled multiple tumor-cell lines as effectively as hnRNP A2/B1 monoclonal antibodies. When conjugated with fluorescent carbon nanodots (CDots) it could freely enter multiple living tumor cell lines (HepG2, MCF-7, H1299, and HeLa), whose growth it inhibited by targeting hnRNP A2/B1. Similar inhibitory effects were observed when the GFP-HepG2 hepatocarcinoma cells treated with C6-8-conjugated CDots were implanted in nude mice. Our work provides a new aptamer for targeting/labeling multiple tumor cell types, and its nanoparticle conjugates bring further advantages that increase its potential for use in cancer diagnosis and therapy.